Rhetoric, organizational category dynamics and institutional change: a study of the UK welfare state - Coule, Tracey M.; Bennett, Ellen (2016)
Accounts of institutional change and categorization conventionally assume that high-status change agents can impose change, even to stable category systems, which lower-status actors accommodate in order to ensure social approval and material resources. By exploring the UK Conservative-Liberal Coalition's rhetorical efforts to reform the welfare state, how welfare providers are categorized and the subsequent response of implicated category members, we offer instead an account of institutional change that exposes the agentic limitations of high-status actors. While governments may well be in a position to impose changes in the formal rules of the game through manipulation of material resources (fiscal contraction, privatization, open markets, deregulation), we find that they cannot necessarily monopolize symbolic resources (identities/cultural features). We also find that deviation from cultural expectations is available not only to large, high-status organizations; low-status actors too have discretion over their responses to institutional pressures regarding how they are categorized and subsequently judged. - Reproduced.
Keywords: Organizational change